(untitled) (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstrac: Public participation in policy development in countries that implement democracy including in Indonesia is not new. Public participation is a process to provide technical opportunities and broader authority to the community together to solve various problems. As a concept and practice of development, the concept of participation recently discussed in the 1960s when various international institutions promote participation in the practice of planning, implementation, and evaluation of development. This research was conducted at 9 : 1 the village chief informant. 1 sysop BPD, sysop LPM, 1 religious figures, and 5 members of the public. The techniques of data collection is done by way of interviews, observation and documentation. And data analysis techniques used are information gathering, data presentation, data reduction and withdrawal of the conclusion. Keywords : public participation, development, infrastructure